Current Landscape of Temporary Percutaneous Mechanical Circulatory Support Technology - Rani Upadhyay; Hussayn Alrayes; Scott Arno; Milan Kaushik; Mir B Basir (US Cardiology Review)
Mechanical circulatory support devices provide hemodynamic support to patients who present with cardiogenic shock. These devices work using different mechanisms to provide univentricular or biventricular support. There is a growing body of evidence supporting use of these devices as a goal for cardiac recovery or as a bridge to definitive therapy, but definitive, well-powered studies are still needed. Mechanical circulatory support devices are increasingly used using shock team and protocols, which can help clinicians in decision making, balancing operator and institutional experience and expertise. The aim of this article is to review commercially available mechanical circulatory support devices, their profiles and mechanisms of action, and the evidence available regarding their use.